PSYCHOLOGICAL PECULIARITIES OF ADAPTIVITY IN AFRICAN STUDENTS - L I Badalova (Peoples' Friendship University of Russia (RUDN University), 2015)
The article analyzes the results of the empirical research of adaptability as a basic characteristic of a personality; it was conducted on a sample of the representatives of different nationalities of African students. The research was made with the use of the capsule version of the blank methods, elaborated by A.I Krupnov, as well as the qualitative analysis of the adaptability components manifestation and the connections between them with the use of the correlation analysis. The qualitative analysis of the manifestation degree of each adaptability component shows that the adaptation index has the highest ranking. This proves that African students can adjust well to the new social and cultural environment while taking classes. However the respondents showed high levels of nostalgia and detachment. These feelings are accompanied by negative emotions (emotional stress) and prevent a normal integration into the new society. The development of the self-confidence and addressing the affective disposition can be regarded as the major resources for compensation and correction of the negative influence of adaptability weaknesses. At the same time there is a connection between nostalgia and adaptation parameters. This phenomenon is the indicative of a positive role of experiencing a painful homesickness in the process of adaptation of the African students. This refers to the two-directional functional ability of nostalgia and its value for the successful integration into a new society.